Logistics Challenges in Regional Healthcare: A Case Study of RSUD Undata Palu's Medical Equipment Management - Bakri, Suardi; Rusman (Yayasan Sinergi Kawula Muda, 2025)
This study examines the logistics management of medical equipment at RSUD Undata Palu, a regional referral hospital in Central Sulawesi, Indonesia, over the period 2019–2024. The research explores six key components: planning, procurement, storage, distribution, disposal, and control. Using a qualitative descriptive approach, data were collected through in depth interviews, field observations, and document analysis. Findings show that while digital integration has improved procurement transparency and semi automated distribution processes, challenges remain in real time inventory monitoring, inadequate storage conditions, delayed equipment disposal, and limited user engagement with digital tools. Storage constraints and bureaucratic hurdles in disposal processes further compromise logistical efficiency. These gaps affect the availability, reliability, and timeliness of medical services, underlining the strategic importance of logistics in healthcare delivery. The study highlights the need for holistic reform through integrated digital systems, performance tracking, and institutional capacity building. By contextualizing these findings within broader policy and technological frameworks, this research offers practical insights for strengthening logistics governance in developing healthcare systems.